Everyday Qur’an di Era Post-Konsumerisme Muslim - Saputro, M. Endy (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2015)
This paper aims to give a preliminary draft to formulate an innovative concept in the Qur’anic studies world in the age of post-consumerism Muslim. Recent studies on tug of war between globalization and religion have been identifying salient social transformation in some parts of Muslim world, such as the rise of new (media) religious authority, religious commodification trends, varieties of Islamic consumption, the emergence of public Islam and so forth. Apart from these recent scholarships, which successfully grasp the globalization’s influence toward religion (Islam), this paper offers the concept of everyday Qur’an as an alternative basic approach of understanding the cultures of Qur’an in this changing (Muslim) world and at the same time, seeking to briefly explain its emerging issues. Some exemplary issues then have analytically discussed to reflect how the proposed theory applied. Thus, everyday Qur’an can contribute the discourse of cultures based technology in the context of Qur’anic Studies.